Mitochondrial creatine kinase: a major constituent of pathological inclusions seen in mitochondrial myopathies. - Stadhouders, A M (1994)
Overaccumulation of abnormally organized mitochondria in so-called "ragged-red" skeletal muscle fibers is a morphological hallmark of mitochondrial myopathies, in particular of mitochondrial encephalomyopathies. Characteristic for the abnormal mitochondria is the occurrence of highly ordered crystalline inclusions. Immuno-electron microscopy revealed that these inclusions react heavily with specific antibodies against mitochondrial creatine kinase (Mi-CK). Image processing of selected crystalline inclusions, sectioned along the crystallographic b, c planes, resulted in an averaged picture displaying an arrangement of regular, square-shaped particles with a central cavity. The overall appearance, dimensions, and symmetry of these building blocks are very reminiscent of single isolated Mi-CK octamers. Taking these findings together, it is concluded that Mi-CK octamers indeed represent the major, if not the only, component of these mitochondrial inclusions.